Development of Bypass Evacuation Route Setting Method Considering the Flood Depth - Soo Lee, Ji; oon, Yoon (International Journal of Engineering and Technology, 2018)
The purpose of this study is to develop a method of setting the route by bypassing an area where evacuation is impossible due to the flooding depth in a single global scale range. Most evacuation route guidance maps developed so far have a broader range of analysis than the actual evacuation area, suggesting only a rough evacuation direction. In addition, recent map inspection showed that evacuation cannot be conducted in reality due to the fact that evacuation routes are excluded from actual evacuation routes. In order to solve this problem, this study drew out areas where physical evacuation is impossible and has developed a bypass route setting method. In addition, it applied the developed method to the flood area and verified to confirm that it is possible to provide a concrete route for each step of flooding by simulating the progress of flooding successively. In order to commercialize the results of the research in areas prone to floods in the country, it is necessary to establish a methodology to automate and construct route information.Â Â